Numerical investigation of a wave glider in head seas. (15th September 2018) - Yang, Fuming; Shi, Weichao; Zhou, Xu; Guo, Bin; Wang, Dazheng
Abstract: A wave glider comprises a surface boat, which harvests energy from wave and solar power, a submerged glider containing six pairs of tandem hydrofoils and a tether connecting them in between. This paper presents a numerical simulation to predict the wave glider dynamic performance in head seas with the aid of computational fluid dynamic (CFD) method. The simulation involves two commercial CFD software packages, FINE/Marine and STAR-CCM+. Firstly, unsteady Reynolds Averaged Navier-Stokes (URANS) simulation was built in FINE/Marine with volume of fluid (VOF) model to simulate the flow around the surface boat and the tandem hydrofoils as a system, followed by the high-fidelity simulation of the passive eccentric rotation of the underwater tandem hydrofoils in STAR-CCM + using overset mesh. By taking the advantages of both softwares, manual iteration was conducted to achieve a converged result. Consequently, by analyzing these results, the surge force acting on the surface boat and the passive eccentric rotation law of the hydrofoils have been achieved which are proved to be the main factors affecting the propulsion efficiency of the wave glider. Highlights: A numerical simulation to predict the wave glider motions in head seas is proposed. Passive eccentric rotation of the wave glider's tandem hydrofoils has been firstly modelled. The response of the wave glider in head seas is acquired. The main factors affecting the hydrofoil propulsion efficiency of the wave glider are determined.